Sustained release of a highly specific GSK3β inhibitor SB216763 in the PCL scaffold creates an osteogenic niche for osteogenesis, anti-adipogenesis, and potential angiogenesis - Gong, Weimin; Li, Molin; Zhao, Lizhou; Wang, Pengtao; Wang, Xiaofang; Wang, Bo; Liu, Xing; Tu, Xiaolin (Frontiers in Bioengineering and Biotechnology, 2023)
The safe and effective use of Wnt signaling is a hot topic in developing osteogenic drugs.SB216763 (S33) is a widely used highly specific GSK3β inhibitor. Here, we show that S33 initiates canonical Wnt signaling by inhibiting GSK3β activity in the bone marrow stromal cell line ST2 and increases osteoblast marker alkaline phosphatase activity, osteoblast marker gene expression including Alpl, Col1α1, and Runx2, promoting osteogenic differentiation and mineralization of ST2 cells. In addition, S33 suppressed the expression of adipogenic transcription factors Pparg and Cebpa in ST2 cells to suppress adipogenesis. ICRT-14, a specific transcriptional inhibitor of Wnt signaling, reversed the effects of S33 on the differentiation of ST2 cells. S33 also increased the expression of osteoclast cytokines RANKL and Opg but decreased the RANKL/Opg ratio and had the potential to inhibit osteoclast differentiation. In addition, we printed the PSCI3D（polycaprolactone, S33, cell-integrated 3D）scaffolds using a newly established integrated 3D printing system for hard materials and cells. S33 sustained release in the hydrogel of the scaffold with 25.4% release on day 1 and 81.7% release over 7 days. Cells in the scaffolds had good cell viability. The ratio of live/dead cells remained above 94% for seven days, while the cells in the scaffolds proliferated linearly, and the proliferative activity of the PSCI3D scaffold group increased 1.4-fold and 1.7-fold on days 4 and 7, respectively. Similarly, in PSCI3D scaffolds, osteogenic differentiation of st2 cells was increased. The alkaline phosphatase activity increased 1.4- and 4.0-fold on days 7 and 14, respectively, and mineralization increased 1.7-fold at 21 days. In addition, PSCI3D conditioned medium promoted migration and tubulogenesis of HUVECs, and S33 up-regulated the expression of Vegfa, a key factor in angiogenesis. In conclusion, our study suggests that S33 functions in osteogenesis, anti-adipogenesis, and potential inhibition of osteoclast differentiation. And the sustained release of S33 in PSCI3D scaffolds creates a safe osteogenic niche, which promotes cell proliferation, osteogenesis, and angiogenesis and has application prospects.